Synthesis of gold nanospheres and nanotriangles by the Turkevich approach - Shankar, S. S.; Bhargava, S.; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2005)
Gold nanoparticles of triangular morphology possess interesting optical properties with potential application in medicine and infrared absorbing coatings, however, little is known about conditions that favor their growth. In this paper, we have reinvestigated a time-tested recipe for the formation of gold nanospheres by citrate reduction of aqueous gold ions under boiling conditions (Turkevich recipe). Our principle findings are that gold nanotriangle formation is kinetically controlled and is highly favored at low temperatures. Furthermore, the presence of chloride ions from the precursor chloroaurate ions plays a major role in promoting the growth of [111] oriented triangular/truncated triangular particles. The presence of bromide and iodide ions that possess the ability to replace surface-bound chloride ions inhibits triangle formation to varying degrees.
Keywords: Crystal growth; Gold; halides; nanospheres; nanotriangles; Temperature effect

Scanning tunneling microscopy/spectroscopy on Au nanoparticles assembled using lauryl amine (LAM) and octadecane thiol (ODT) - Datar, Suwarna; Chaudhary, Minakshi V.; Sastry, Murali; Dharmadhikari, C. V. (Applied Surface Science, 2007)
In this report, we demonstrate scanning tunneling microscopy and spectroscopy on thin filins of lauryl amine (LAM) and octadecane thiol (ODT) protected gold nanoparticles. We show that the zero current in the I-V curves (measure of Coulomb blockade (CB) of the nanoparticles) depends on the properties of the spacer molecule. In both the cases the gap voltage and the tunneling current at which the images are obtained are quite different which is further confirmed from the fitting performed based on the orthodox theory. The values for the capacitance and charging energy obtained from the fitting for ODT capped particles are comparable to the values obtained using spherical capacitor model. In contrast, values of these parameters were found to differ for LAM capped nanoparticles. While imaging, ODT capped nanoparticles were observed to drag along the scan direction leading to ordering of particles. Images of LAM capped gold nanoparticles show local ordering in self-assembly of particles although no evidence of large scale ordering in spatial Fourier transform was seen. These observations suggest that nanoparticles with larger CB would be intaged nonevasively in contrast to small CB systems for which tip induced effects will be dominant. In both the systems the current was found to rise faster than theoretical curves based on the orthodox theory suggesting that mechanism of charge transfer in this case may involve field emission rather than tunneling through a rectangular barrier. An attempt has been made to explain charge transfer based on Fowler-Nordheim (F-N) plots of the I-V curves. (c) 2006 Elsevier B.V All rights reserved.
Keywords: Nanostructures; scanning tunneling microscopy (STM)

Spider silk as an active scaffold in the assembly of gold nanoparticles and application of the gold-silk bioconjugate in vapor sensing - Singh, Amit; Hede, Shantesh; Sastry, Murali (Small, 2007)
Spider silk is being viewed with interest by materials scientists due to its excellent resilience and mechanical properties. In this paper we show that spider silk is an excellent scaffold for the one-step synthesis and assembly of gold nanoparticles. Formation of a gold nanoparticle-spider-silk bioconjugate material is accomplished by simple reaction of the fibers with aqueous chloroauric acid. The gold nanoparticles thus formed are strongly bound to the spider-silk fiber surface enabling study of the electrical properties of the nano bioconjugate. Using the well-known contraction/expansion behavior of the fibers in solvents of varying polarity, we show that exposure of the gold nanoparticle-spider silk bioconjugate to vapors of methanol and chloroform leads to changes in electrical transport through the nanoparticles and thus, the possibility of developing a vapor sensor. The bioconjugate shows excellent response time and cycling efficiency to methanol vapors. The activation energy of electron transport from one gold nanoparticle to another in the nanobiocojugate was determined from temperature-dependent electron-transport measurements to be approximately 1.7 eV.
Keywords: bioconjugates; Gold; Nanoparticles; sensors; spider silk

Shape and size selective separation of gold nanoclusters by competitive complexation with octadecylamine monolayers at the air-water interface - Pasricha, Renu; Singh, Amit; Sastry, Murali (Journal of Colloid and Interface Science, 2009)
The paper presents a time-dependent study of shape-dependent preferential complexation of gold nanoparticles to the octadecyl amine (ODA) monolayers at the air-water interface. Room temperature reduction of chloroaurate ions using lemon grass leaf extract yields a Mixture of spherical and triangular nanoparticles, which were used for this study. These nanoparticles have a net negative charge on their surface due to the presence of biomolecules from plant extract and thus a strong attractive electrostatic interaction with the positively charged ODA monolayers drives the complexation process. The extent of preferential complexation of the gold nanoparticles to the ODA monolayers is a function of the charge on the particles and the relative mobility of the nanoclusters in the medium. The complexation process has been followed in real time by a host of techniques such as surface pressure-area (pi-A) isotherms, UV-vis-NIR spectroscopy and Brewster angle microscopy. The charge and mobility of the gold nanoparticles was confirmed by measurement of their electrophoretic mobility. Langmuir-Blodgett films of the nanogold-ODA composites have been characterized by UV-vis-NIR spectroscopy, Fourier transform infrared spectroscopy, and transmission electron microscopy. These measurements clearly indicate that the cluster mobility and complexation increase with decreasing cluster size. In the competitive complexation process of large and small gold particles, it was observed that some bigger gold particles were also incorporated into the amine matrix even though the cluster mobility is higher for smaller gold particles. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: Competitive complexation; gold nanoparticles; Langmuir-Blodgett technique; ODA monolayer

Synthesis of catalytically active porous platinum nanoparticles by transmetallation reaction and proposition of the mechanism - Pasricha, Renu; Bala, Tanushree; Biradar, Ankush V.; Shubhangi B. Umbarkar; Sastry, Murali (Small, 2009)
A facile method for the synthesis of porous platinum nanoparticles by transmetallation reactions between sacrificial nickel nanoparticles and chloroplatinic acid (H(2)PtCl(6)) in solution, as well as at the constrained environment of the air water interface, using a Langmuir-Blodgett instrumental setup is presented. To carry out the transmetallation at the air-water interface hydrophobized nickel nanoparticles are assembled as a monolayer on the sub phase containing platinum ions. The porous Pt nanoparticles obtained as a result of the reaction are found to act as extremely good catalysts for hydrogenation reaction. The products are well characterized by TEM, HRTEM, EDAX, and STEM. Attempts are made to postulate the plausible mechanism of this reaction to generate this kind of nanoparticle with controllable geometric shape and structure. This simple strategy has the potential to synthesize other nanomaterials of interest too.
Keywords: Catalysts; Interfaces; Nickel nanoparticles; porous platinum; Transmetallation